Estimating the effectiveness of gold and iron oxide nanoparticles for hepatocellular carcinoma ablation therapy: a meta-Analysis - Janairo, Jose Isagani B. (Animo Repository, 2020)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality worldwide, wherein treatment still remains a challenge. A promising experimental treatment for tumors that can potentially overcome some of the limitations faced by conventional therapies for HCC is nanoparticle – mediated hyperthermia (NMH). Currently at the developmental stage, NMH usually utilizes gold or iron oxide nanoparticles to convert radiofrequency or alternating magnetic field into heat that causes targeted cell death. In order to assess the effectiveness of NMH on a greater scale, and in the face of varying levels of effectiveness in published literature, this meta-analysis was conducted. A systematic literature search identified relevant studies in gold and iron oxide NMH for HCC cell lines published from 2008 – January 2019. Seven studies met the inclusion criteria, wherein three studies used gold NMH, and the remaining four used iron oxide NMH. Outcome of interest is cell viability after irradiation in the presence of the nanoparticles. A pooled risk ratio with 95% confidence interval (CI) was calculated using a random effects model. Iron oxide – based NMH was able to decrease HCC cell viability by 87% while 19% for gold-based NMH. Moderate to high heterogeneity is attributed to the different classes of nanoparticles, concentration, cell lines, and irradiation duration used in the pooled studies. The results provide encouraging insights for the continuous development of NMH for cancer treatment. Considering that iron oxide is more cost-effective than gold nanoparticles, focusing on the development of iron oxide nanoparticles for this nanomedical technology may accelerate the development and clinical application of NMH. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.